AL-ALLAMEH MUHAMMAD MAHDI AL-ASFI AND THE JURISPRUDENTIAL AND FUNDAMENTAL RENEWAL - AL-DARRAJI, WAHAB; AL-BADRI, HUSSEIN (Al-Adab Journal, 2023)
Allameh Muhammad Mahdi Al-Asefi put forward innovative and creative ideas in various scientific fields and an original idea, and he excelled in it including", the principles of jurisprudence and conduct science, ethics and its effects on the education of the individual and society and the liberal arts such as history and philosophy, political science, sociology and education. In presenting his scientific idea and expression, Allameh Al-Asefi combined two theological approaches based on analysis, reflection, deep contemplation, precise understanding and academic approach in liberal arts theorizing and modern scientific knowledge, and the combination of these two have included wide and excellent results. Until his scientific talents enabled him to attain the degree of ijtihad, as well as a master’s degree in academic sciences. His innovations were not limited to the idea, but rather extended to methodology and method. As for the methodology, the methodology of the Allameh is distinguished by broad tracking and complete understanding of the idea, as well as great depth and long meditation on it, benefiting from the successful seminary and academic methodology and mixing them in extracting the successful idea, interesting style and the clear demand. In this article, we discuss two important fields that Allameh introduced and excelled in and renewed in them, namely the jurisprudential field and the fundamentalist field. The article is summarized in these two fields.